Disability prevalence in midlife (aged 55-65 years): Cross-Country comparisons of gender differences and time trends - Serena Wang; Drystan Phillips; Jinkook Lee (BMC, 2021)
Abstract Background Prior literature on disability has centered on disability prevalence among older adults ages 65 and older, providing only limited insight to potential gender differences in disability prevalence in mid-life. Midlife is, however, a critical time to be examined, as it is typically the time in the life course when large inequalities in physical health first emerge. Methods Using the Harmonized data files provided by the Gateway to Global Aging Data, we estimate disability prevalence of nationally representative adults ages 55-65 from 23 countries (N = 79,465). We examine gender differences in two disability indicators, limitations in instrumental activities of daily living (IADLs) and activities of daily living (ADLs) in two time periods, 2004/05 and 2014/15. Results There are substantial cross-country variations in IADL and ADL disability prevalence in midlife. Within countries, we find that women have higher IADL prevalence than men in only one out of five countries. Similarly, for ADL prevalence, women have higher ADL prevalence than men in only one out of ten countries. Further, comparing disability prevalence in two time periods, we observe different country-specific time trends. Conclusions In the majority of mid and high-income countries, there is no significant gender difference in IADL and ADL prevalence, but there are few countries where women show higher prevalence of disability than men in mid-life. This finding calls for future research into what contributes to cross-country variations.